An online collaborative learning system : designing for evaluation of students' learning - Yahaya, Nazli; Mohamad Razali, Norazila (Universiti Teknologi Malaysia, 2008)
This paper will discuss work-in-progress in the development and evaluation of an online collaborative learning system. The context is a study of a course in an on-campus weekend part-time program attended by students who share similar professional engineering backgrounds but living far apart from each other with no opportunities to meet for discussions between weekends. The course requires students to tackle problems based on real life scenarios within small online groups after having attended lectures over the weekend. The research will look at ways in which group work can be conducted, and the contribution of the instructor. The approach to be taken will be an interpretive case study using questionnaire survey, text analysis and interviews. The main findings from the study will be reported, with focus on the strengths of, and difficulties in, using the research methods.